2013
DOI: 10.1590/s1517-83822013005000046
|View full text |Cite
|
Sign up to set email alerts
|

Screening of efficient arbuscular mycorrhizal fungi for Azadirachta indica under nursery condition: a step towards afforestation of semi-arid region of western India

Abstract: To optimize nursery practices for efficient plant production procedures and to keep up to the ever growing demand of seedlings, identification of the most suitable species of arbuscular mycorrhizal fungi (AMF), specific for a given tree species, is clearly a necessary task. Sixty days old seedlings of Neem (Azadirachta indica A. Juss) raised in root trainers were inoculated with six species of AMF and a mixed inoculum (consortia) and kept in green house. Performances of the treatments on this tree species were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Arbuscular mycorrhizal fungi may also interact with each other synergistically. It was experimentally found out that AMF effects are greater when AMF consortia inoculums are applied than single AMF ( Banerjee et al, 2013 ). After long years of observation, Barea et al (2011) concluded that the use of native AMF consortia has the maximum effect.…”
Section: Amf and The Mycorrhizosphere Ecologymentioning
confidence: 99%
See 2 more Smart Citations
“…Arbuscular mycorrhizal fungi may also interact with each other synergistically. It was experimentally found out that AMF effects are greater when AMF consortia inoculums are applied than single AMF ( Banerjee et al, 2013 ). After long years of observation, Barea et al (2011) concluded that the use of native AMF consortia has the maximum effect.…”
Section: Amf and The Mycorrhizosphere Ecologymentioning
confidence: 99%
“…Meanwhile, AMF inoculation has proved to be effective under wide range of soil conditions ( Janos, 1980 ; Brundrett and Abbott, 2002 ) including on soils with good AMF abundance (e.g., Banerjee et al, 2013 ). Positive AMF effect is not ensured by the presence of abundant indigenous AMF but by both abundance (quantity) and efficiency (quality) of indigenous fungal populations ( Onguene and Kuyper, 2005 ).…”
Section: Amf Biotechnology For the Restoration Of Degraded Landsmentioning
confidence: 99%
See 1 more Smart Citation
“…The perusal of data in Table-1 indicated that root growth parameters of Ailanthus excelsa like root length, fresh root weight and dry root weight were found significantly higher in treatment containing FS + FYM+A.S whereas, shoot parameters like shoot length, fresh shoot weight dry shoot weight, collar diameter and number of leaves were found significantly higher in treatment containing FS + FYM + G.I as compared with control after three and six months of growth of Ailanthus excelsa seedlings and other treatments under studied. Growth parameters of Azadirachta indica was found significantly higher when treated with mycorrhiza fungi over control reported by Banerjee et. al (2013).…”
Section: Resultsmentioning
confidence: 52%
“…), attacked by M. javanica. (Mwangi et al, 2011;Marro et al, 2014;Banerjee et al, 2013). The AMF, applied on G. intraradices increased plant height, leaf and root dry biomass, panicle length, and protein content in the grain of sorghum (Diaz-Franco et al, 2008).…”
Section: Arbuscular Mycorrhizal Fungi (Amf)mentioning
confidence: 99%